Kajian Ikonografi Arca Berserban pada Beberapa Pura di Kabupaten Karangasem, Bali - Palupi Titasari, Coleta; Srijaya, I Wayan (Humanis; Vol 28 No 1 (2024)DO - 10.24843/JH.2024.v28.i01.p09, 2024)
Identification of types and forms of archaeological statues can be found by the iconographic characteristics that define the identity of the figures being portrayed. Karangasem, Bali is one area that has remains of statues with intriguing iconographic characteristics, that is, the portrayal of figures using turban as a head covering. This kind of statue portrayal is rarely found in Bali and in Indonesia. The existence of several statues with turban indicates a certain concept regarding the characterization of the turbaned figure. This research was aimed to analyze the statues distributed in several temples in Karangasem, Bali. The method used consists of collecting data and analyzing data. The statues are iconographically analyzed. Analysis is conducted in two ways, which are morphology and technology. The results showed that the statues are the embodiment of religious figures that prove the existence of religious figures in ancient Balinese society.